Do orally administered antibiotics reach concentrations in the middle ear sufficient to eradicate planktonic and biofilm bacteria? A review. Issue 3 (March 2015) - Belfield, Katherine; Bayston, Roger; Birchall, J.P.; Daniel, Matija
Abstract Introduction Infectious conditions of the middle ear are a common and significant cause of morbidity and mortality worldwide. Systemic antibiotics are frequently used, but their effectiveness will depend on whether an adequate antibiotic concentration is achieved in the middle ear; this is especially important in biofilm infections such as otitis media with effusion (OME), where high antibiotic concentrations are typically required for effective treatment. Objective This review examines what antibiotic levels can be reached in the middle ear with oral administration, as a means of guiding rational antibiotic choice in the clinic and future research, and to determine whether levels high enough for biofilm eradication are reached. Methods A literature search of studies measuring levels of antibiotics in the plasma and in the middle ear after oral administration was conducted. These levels were compared to the minimum inhibitory concentrations (MIC) provided by the European Committee for Antimicrobial Susceptibility Testing (EUCAST) to determine if antibiotic doses were reaching sufficient levels to inhibit planktonic bacteria. The middle ear concentrations were then calculated as a multiple of the MIC to determine if the concentrations were reaching biofilm eradication concentrations (typically up to 1000 × MIC). Results The highest antibiotic levels against Staphylococcus aureus reach 8.3 × MIC, against Moraxella catarrhalis 33.2 × MIC, against Haemophilus influenzae 31.2 × MIC, and against Streptococcus pneumoniae 46.2 × MIC. The macrolide antibiotics reach higher levels in the middle ear than in plasma. Conclusions Orally administered antibiotics reach levels above the MIC in the middle ear. However, they do not reach levels that would be likely to eradicate biofilms.